(untitled) (Journal of Pharmaceutical Negative Results, 2022)
INTRODUCTION: Composite restoration/composite filling is a tooth colored plastic and glass mixture used to restore decayed/carious teeth. The aim of this study is to evaluate the knowledge, attitude and practice of finishing and polishing of composite restoration among dental students.MATERIALS AND METHOD: A questionnaire of 10 questions was created and entered in the online survey creator ‘Google Forms’ and shared among each student of about 100 individually and data were collected subject to statistical analysis using SPSS software. Statistical tests used were descriptive statistics and Chi square tests. P value less than 0.05 was considered statistically significant.RESULT: Results of this study suggest that dental students were having more knowledge ,awareness and practice of finishing and polishing of composite restoration among dental studentsCONCLUSION: From the study it is concluded that the participants have adequate knowledge, attitude and practice about finishing and polishing the composite restoration except 1st yrs who lack practice and attitude